Role of Mycorrhizal fungi in Reduction of Water Stress for Growth and yield of Mung bean (Vigna radiata L.): maytham abbas - AL-Karhi, Mytham Abbas Jawad (Journal of Kerbala for Agricultural Sciences, 2018)
A field experiment was conducted in the autumn season of 2017 in a field of Hindia on the Mungbean plant Vigna radiate L. a local cultivar to study the interaction effect of both the Mycorrhizal fungi (Glomus mosseae) Under levels of irrigation periods 5, 10,15 days. The experiment was in the order of Split Plot with Randomized Complete Block Design with three replicates. Irrigation treatments were randomly distributed to the main plot, while the biological fertilization treatments were distributed on secondary plates. The experiment 5 treatments resulting from treatments (Chemical fertilization), (mycorrhizal inoculation) at three periods of irrigation which are irrigation every 5 , 10 , 15 days and three replicates. Results can be summarized as follows: The irrigation treatment of irrigation every 5 days was superior in having the highest mean of plant height, leaf area, relative water content of leaves. Which were 49.32 cm, 601.20 cm2.Plant-1, % 55respectively. This treatment was also given achieved the highest values of yield and its components number of pods per plant, number of seeds pod per, seeds yield which were 28.70 pods.Plant-1, 8.50 seed.pod-1, 3.81 tons.ha-1 respectively. The treatment of Bio-fertilizer mycorrhiza achieved superiority for all studied traits of plant height, leaf area, relative water content of leaves which were 54.87cm , 685.8cm2.plant-1,81.51%, respectively. The treatment was also shown superiority in all yield and its components number of pods per plant, number of seeds per pod , seeds yield. Amount ( 33.64 pods. Plant-1 , 8.42 seed .pod-1, 4.00 tan .ha-1) respectively, Which outperformed significantly on all Bio fertilizer transactions. Key word: Mung bean, Irrigation Treatments, Mycorrhiza